Antibody-Induced Acute Factor X Deficiency: Clinical Manifestations and Properties of the Antibody - Vijaya Mohan Rao, L; Zivelin, Ariella; Iturbe, Ignacio; Rapaport, Samuel I (Thrombosis and Haemostasis, 1994)
A patient is described with serious bleeding due to a transient selective deficiency of factor X. Crossed immunoelectrophoresis of patient’s plasma with anti-factor X antibody revealed an abnormal factor X arc suggestive of the presence of plasma factor X/anti-factor X immune complexes. A similar abnormal arc was obtained on adding the patient’s IgG to normal plasma. Immunoblotting of factor X after reduced SDS-PAGE revealed that the patient’s IgG bound to the light chain of intact factor X but not Gla-domainless factor X. The patient’s IgG inhibited activation of factor X by Vila/tissue factor (TF), by IXa/VIIIa/phospholipid complex, and by Russell’s viper venom. The IgG failed to inhibit the proteolytic activity of factor Xa towards a chromogenic substrate. However, under reaction conditions of limited factor Xa availability, the IgG could be shown to impair hemostatic functions of factor Xa that require the participation of its light chain: activation of prothrombin by prothrombinase; activation of factor VII bound to TF; and inhibition of VIIa/TF activity by factor Xa/tissue factor pathway inhibitor complexes. A few earlier patients have been described with transient, selective factor X deficiency and serious bleeding, but in only one was evidence obtained of an antibody against factor X. It will be of interest to learn whether use of the techniques described in this report will permit the identification of immunoglobulin with similar binding and functional properties in future patients with this rare syndrome.